A prospective study of obstetric and gynaecological emergencies in a tertiary care hospital - Jindani, Shahna Anishbhai; Sailor, Asha Bhagwatibhai; Modi, Dipti A.; Kaul, Somika; Rami, Bijal D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The management of obstetrics and gynaecological emergency is directed at the preservation of life, health, sexual function and the perpetuation of fertility. The main aim of the study was to access the burden of surgical emergency and to study the course of management at a tertiary care hospital. Methods: This prospective study was carried out in the department of obstetrics and gynaecology, S. S. G. Hospital, Baroda for a period from January to December 2018. Results: A total of 73 patients presented to our emergency room who required urgent surgical intervention. All patients were resuscitated and surgery was done at earliest possible time. The age of patient ranged from 18 to 45 years. About 75.8% of female presented with the complaint of acute abdomen, followed by 32.9% with bleeding per vaginum. 16.4% had vomiting, 6.8% with fever and 4.1% with mass per abdomen. In majority of cases a diagnosis of ruptured ectopic pregnancy (34 patients) was made, followed by PPH in 14 patients and 12 cases of rupture uterus. Four cases of torsion of ovarian mass and 3 cases of septic peritonitis were operated. The most common surgery performed was salpingectomy followed by subtotal obstetric hysterectomy. A mortality rate of 8.2% was noted. Conclusions: This study emphasized the great role of timely surgical intervention as lifesaving procedures. Skilled clinicians and immediate intervention in a tertiary care is the main-stay of the emergency case management and are indispensable for decreasing mortality and morbidity.